(untitled) (International Association of Biologicals and Computational Digest, 2022)
Deltamethrin (DLM) is a widely used pyrethroid, pest control insecticide due to restriction on the sale of organophosphate. Deltamethrin (DLM) being a potent hepatotoxic compound, that affects physiological functions of liver; however, the implications of the hepatotoxic effects of DLM on the mammalian system and its influence on the hepatic enzymatic activity are still unclear. Curcumin (CUR), a major polyphenol component of Curcuma longa Linn, is a potent antioxidant often used in traditional medicine as an ameliorative agent. However, its underlying mechanism as an anti-oxidant against DLM-toxicity remains unknown. Hence, the present study has been designed to determine the binding affinity of DLM to a hepatic enzyme marker such as Aspartate aminotransferase (AST). Moreover, the study is aimed to delineate the role of CUR on DLM-induced hepatotoxic effects through a computational approach. The molecular docking carried out demonstrated that CUR manifests a stronger binding affinity towards the liver marker enzyme, AST as compared to deltamethrin. This could explain the possible mechanism for inhibition of the toxic influence of DLM- induced reactive oxygen species on liver enzyme activity. Thus, this computational evidence validates the tenet that CUR displays anti-oxidative properties for attenuation of DLM induced hepatotoxicity, alteration in the mechanism of liver marker enzyme and its subsequent impact on hepatic tissue.